2019
DOI: 10.1126/science.aaw5842
|View full text |Cite
|
Sign up to set email alerts
|

Social transmission of food safety depends on synaptic plasticity in the prefrontal cortex

Abstract: When an animal is facing unfamiliar food, its odor, together with semiochemicals emanating from a conspecific, can constitute a safety message and authorize intake. The piriform cortex (PiC) codes olfactory information, and the inactivation of neurons in the nucleus accumbens (NAc) can acutely trigger consumption. However, the neural circuit and cellular substrate of transition of olfactory perception into value-based actions remain elusive. We detected enhanced activity after social transmission between two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Ross and Eichenbaum (2006) reported that memory retrieval of social transmission of food preference is associated with increased Fos expression in the Pir (and OFC). Loureiro et al (2019) showed a critical role of a Pir to prefrontal cortex projections in this behavior. Acquisition of conditioned flavor preference is associated with increased Fos expression in the Pir (Mediavilla et al, 2016), and lesions or antagonists of NMDA or cannabinoid type 1 receptors decrease conditioned flavor preference (Mediavilla et al, 2016;Mukherjee and Yuan, 2016;Terral et al, 2019).…”
Section: Role Of Pir and Projections Between Pir And Ofc In Relapse Tmentioning
confidence: 92%
“…Ross and Eichenbaum (2006) reported that memory retrieval of social transmission of food preference is associated with increased Fos expression in the Pir (and OFC). Loureiro et al (2019) showed a critical role of a Pir to prefrontal cortex projections in this behavior. Acquisition of conditioned flavor preference is associated with increased Fos expression in the Pir (Mediavilla et al, 2016), and lesions or antagonists of NMDA or cannabinoid type 1 receptors decrease conditioned flavor preference (Mediavilla et al, 2016;Mukherjee and Yuan, 2016;Terral et al, 2019).…”
Section: Role Of Pir and Projections Between Pir And Ofc In Relapse Tmentioning
confidence: 92%
“…Especially, when confronted to food scarceness, behavioral tradeoffs need to be made 2,3 . Olfactory senses play an important role in this process as they help to find food but also to sense and avoid threatening situations [4][5][6][7][8][9] such as predation. For rodents, the attraction to food is primarily determined by familiarity, as scents of known food are innately favored 2,10 .…”
mentioning
confidence: 99%
“…These scents are detected by olfactory sensory neurons (OSNs) found in the main olfactory epithelium (MOE) 11,12 . Food familiarity can be acquired via communication between individuals, by the so-called "social transmission of food preference" (STFP), a behavioral process that occurs by sniffing the breath of conspecifics and making an association between the novel food scent and the presence of the endogenously produced carbon disulfide gas (CS 2 ) 4,13,14 . For this process to occur, the concomitant recognition of the food odorant by OSNs and the detection of the CS 2 by guanylyl cyclase-D neurons (GC-D) of the MOE is essential.…”
mentioning
confidence: 99%
“…*p < 0.05 versus innate cumin preference. Ross et al, 2005) and damage or dysfunction at any level in this circuit seems to have disruptive consequences on STFP acquisition or recall (Brightwell et al, 2005;Bunsey and Eichenbaum, 1995;Jeon et al, 2007;Loureiro et al, 2019;Peters et al, 2003;Ross and Eichenbaum, 2006;Ross et al, 2005). Therefore, information exchange between cortical and hippocampal modules underlying systemic consolidation could occur in this circuitry, which does not require the ReRh nuclei hub.…”
Section: Discussionmentioning
confidence: 99%
“…Lesburguères et al (2011) also showed that upon information encoding, OFC neurons undergo a tagging process, which might serve as a matrix for hippocampus-driven cortical rewiring supporting enduring memory. Recently, Loureiro et al (2019) found STFP to depend on projections from the piriform cortex—one of the olfactory projection areas to which the study by Ross and Eichenbaum had pointed—to the neurons of the mPFC (prelimbic and infralimbic regions), which project onto the nucleus accumbens. Thus, STFP seems to involve several distributed and interdependent structures of the brain.…”
Section: Discussionmentioning
confidence: 99%